The Sobieskis: Memories, Prints, Paintings, and Letters in the Collections of the Sovrintendenza Capitolina di Roma, in the Roman Chronicles and in Rome: A Historical Commentary .......... 385 - Ceci, Francesca (Collecting Antiquities from the Middle Ages to the End of the Nineteenth Century: Proceedings of the International Conference Held on March 25-26, 2021 at the Wrocław University Institute of Art History, 2021)
This article presents two marble epigraphs preserved in the Musei Capitolini, one that mentions King Jan III Sobieski, and the other dedicated to his wife, Maria Casimira, along with other iconographic and documentary material related to the Sobieskis in Rome in the Museo di Roma and the archival heritage of the Sovrintendenza Capitolina.